Pemanfaatan Media Digital Salam TV Dalam Kegiatan Dakwah Bagi Mahasiswa di Sumatera Utara - Pratama, Dimas; Mutiawati, Mutiawati (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Digital da'wah is one solution to increasing understanding of religion. This has certainly provided a new perspective in the development of the world of da'wah. The ease of accessing and obtaining information is one of the reasons for the existence of digital da'wah. However, despite the conveniences offered, it turns out there are several problems that must be faced. Not being wise in using technology often has serious consequences for its users. This research wants to find out how effective the use of digital media Salam TV is in da'wah activities to increase understanding of religion among students in North Sumatra, especially at the North Sumatra State Islamic University (UINSU). This research data comes from digital literature, such as journals, websites and online documents. The research approach uses a qualitative approach by applying the phenomenological method as a methodological basis. Data collected from various sources is then reduced and constructed into a new, more complete concept. The data analysis carried out adapted qualitative data analysis techniques. The research results show that the use of Salam TV digital media in da'wah activities must be supported by good collaboration between preachers, media and students in order to increase understanding of religion. Apart from that, it is important to have ongoing da'wah activities so that they can continue to motivate students to understand religious learning as a whole.